The Influence of Celebrity Endorsement and Product Quality on Purchase Decisions of MS Glow Skincare Products in Bandung: The Mediating Role of Brand Image - Aulia, Serina (DINASTI RESEARCH, 2025)
This study explores the influence of celebrity endorsement and product quality on purchase decisions of MS Glow skincare products in Bandung, with brand image as a mediating variable. The research responds to the increasing popularity of local skincare brands in Indonesia and examines whether celebrity-driven marketing strategies remain effective in a competitive landscape. A quantitative approach was employed by distributing questionnaires to 150 female respondents aged 18–35 in Bandung. Data were analyzed using multiple regression and Sobel test with SPSS 21. The findings reveal that celebrity endorsement significantly enhances brand image, which in turn positively affects purchase decisions. However, celebrity endorsement has no direct effect on purchase decisions unless mediated by brand image. Conversely, product quality has a significant direct impact on purchase decisions but does not significantly affect brand image. These results highlight the importance of managing brand image and delivering high product quality to optimize marketing effectiveness. For brands like MS Glow, a balanced strategy combining emotional branding with functional excellence is essential to maintain consumer loyalty. This research contributes to the understanding of how marketing stimuli influence consumer behavior and suggests further exploration into digital engagement and sustainability perceptions in skincare branding.